PERAN MEDIA, PROFITABILITAS, DAN LEVERAGE DALAM PENGUNGKAPAN EMISI KARBON PADA SEKTOR PERTAMBANGAN : (STUDI EMPIRIS TAHUN 2021-2023) - ‘Aisy, Nadia Rohadatul; Nahar, Aida (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2025)
Introduction: Climate change has become a pressing global issue, sparking intense discussions worldwide. Climate change, as an international phenomenon, has become the most significant environmental challenge currently facing the world. Environmental disclosure related to carbon emissions is still voluntary in Indonesia, and few entities have implemented it. The goal of this study is to analyze the impact of media exposure, profitability, and leverage on carbon emission disclosure by many mining companies listed on the Indonesia Stock Exchange (IDX) between 2021 and 2023.Methods: This study employs a quantitative methodology, selecting research samples through purposive sampling in SPSS software. The focus of this study is on the mining sector listed on the IDX from 2021 to 2023, with research data consisting of financial reports obtained from the IDX website. Results: The study found that the media exposure variable has a significant positive influence on carbon emissions disclosure, as does the profitability variable. Meanwhile, the leverage variable in this study was found to have a significant negative influence on carbon emissions disclosure. Conclusion and suggestion: Media exposure and profitability have been shown to have a significant positive effect on carbon emission disclosure, while leverage has an adverse effect. The measurement index of the dependent variable, which refers entirely to the research by Choi et al. (2013), and the relatively small number of research variables are limitations of this study. Further research is expected to re-examine this by developing several other variables, updating the sample to the latest period, and extending the research period. Keywords: Media Exposure, Profitabilitas, Leverage, Pengungkapan Emisi Karbon